Impact of coronary revascularization on regional artery-specific coronary flow capacity: a serial [15O]H2O positron emission tomography perfusion imaging study. (8th February 2021) - De Winter, RW; Jukema, RA; Van Diemen, PA; Schumacher, SP; Driessen, RS; Stuijfzand, WJ; Bom, MJ; Everaars, H; Van De Ven, PM; Verouden, NJ; Nap, A; Van Rossum, AC; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Coronary flow capacity (CFC) combines absolute hyperemic myocardial blood flow (hMBF) and coronary flow reserve (CFR) in a graphical representation of the severity of myocardial perfusion impairment. Studies evaluating the impact of coronary revascularization on CFC as assessed by [15O]H2O positron emission tomography (PET) are lacking. Purpose. The present study explored the impact of coronary revascularization on regional, artery-specific CFC as assessed by [15O]H2O PET. Methods. A total of 315 patients (mean age 62 ± 10 years) underwent absolute myocardial perfusion imaging at baseline and directly after either percutaneous or surgical coronary revascularization (at 110 ± 50 days). Revascularized perfusion regions were stratified in 3 CFC groups at baseline: severely reduced CFC (defined as myocardial ischemia), moderately reduced CFC and normal CFC. Results. Baseline CFC was severely reduced in 262 vessels (70%), moderately reduced in 95 vessels (25%) and normal in 17 vessels (5%). Regional, artery-specific CFC, hMBF and CFR improved after successful revascularization (P < 0.01). In 127/262 regions, CFC increased from severely reduced to moderately reduced and in 29/262 to normal flow after revascularization (p < 0.01 for both). Additionally, 28/95 revascularized regions increased from moderately reduced to normal flow (P = 0.18). Changes in hMBF (severe vs. moderate vs. normal: 0.84 ± 0.73; 0.41 ± 0.60 and 0.35 ± 0.84 mL·min-1·g-1 ) and CFR (0.92 ± 0.83; 0.49 ± 1.00 and -0.39 ± 1.15) were significantly different comparing baseline CFC groups (both p < 0.01). Furthermore, mixed-model analysis including traditional CAD risk factors revealed that baseline CFC and gender were independent predictors of changes in CFC, hMBF and CFR between baseline and follow-up. Conclusions. Successful revascularization demonstrated a significant and positive impact on regional, artery-specific CFC, hMBF and CFR. Improvements were largest among lower baseline CFC groups. Furthermore, baseline CFC was an independent predictor of change in CFC, hMBF and CFR. These results suggest that the assessment of flow capacity by [15O]H2O PET prior to revascularization may aid in the selection of regions in which absolute myocardial perfusion is most likely to improve.